2015
DOI: 10.1007/s00277-015-2514-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dose reduction of vincristine in R-CHOP on outcomes of diffuse large B cell lymphoma

Abstract: Dose intensity (DI) of chemotherapy affects prognosis of diffuse large B cell lymphoma (DLBCL). Myelotoxicity is the major dose-limiting toxicity (DLT) of most cytotoxic agents for hematological malignancies, whereas DLT of vincristine (VCR) is mainly neurological toxicity. Although VCR is a key drug and its combination with other cytotoxic agents needs consideration, studies focused on relative DI (RDI) of VCR have not been done before. We retrospectively analyzed 86 cases of DLBCL that received six or more c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Initial R-CHOP therapy for DLBCL patients, regardless of age, has been standard of care for the past decade. Maintenance of dose intensity is important in optimizing outcome with this regimen [13][14][15][16]. A variety of studies have been undertaken to improve upon outcome achieved with R-CHOP.…”
Section: Discussionmentioning
confidence: 99%
“…Initial R-CHOP therapy for DLBCL patients, regardless of age, has been standard of care for the past decade. Maintenance of dose intensity is important in optimizing outcome with this regimen [13][14][15][16]. A variety of studies have been undertaken to improve upon outcome achieved with R-CHOP.…”
Section: Discussionmentioning
confidence: 99%
“…Relative dose intensity may also be more heavily dependent on some drugs in the CHOP protocol. Indeed, a relative dose reduction in vincristine has been associated with poorer outcome in human patients diagnosed with diffuse large B‐cell lymphoma treated with R‐CHOP . In a recent study investigating the use of 25‐week CHOP in dogs, the authors suggested a temporal relationship existed between relapse of lymphoma and cyclophosphamide .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a relative dose reduction in vincristine has been associated with poorer outcome in human patients diagnosed with diffuse large B-cell lymphoma treated with R-CHOP. 19 In a recent study investigating the use of 25-week CHOP in dogs, the authors suggested a temporal relationship existed between relapse of lymphoma and cyclophosphamide. 61 Although further investigation is necessary to confirm this observation, efforts could be focused on improving DI of drugs considered most useful for the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This neurotoxicity is a dose-limiting toxicity for vincristine. 7) In their retrospective analysis, Utsu et al 8) demonstrated that a dose reduction in vincristine in patients receiving R-CHOP for diffuse large B cell lymphoma is associated with poor prognosis. 8) Therefore, prevention of vincristineinduced neurotoxicity is important to improve outcomes in patients with non-Hodgkin's lymphoma.…”
mentioning
confidence: 99%